The English Savoury Course. Issue 3 (1st September 2020) - Freedman, Paul; Evans, Joshua
ABSTRACT: The savoury is a course that comes near the end of the meal, after the sweet but before what in Britain is called the dessert (which is usually fruit and nuts as opposed to pastries, puddings and the like which are part of the sweet course). Typically, savouries are salty, spicy or sharp. Cheese straws or ramekins, smoked fish, mushrooms, almost anything on toast are components of classic savouries. The article looks at why this is a peculiarly British preference, its origins in the later Victorian era and its gradual eclipse after the Second World War.